2022
DOI: 10.1001/jamanetworkopen.2022.29532
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy Emergency Department Use and Risks of Severe Maternal and Neonatal Morbidity in Canada

Abstract: IMPORTANCEEmergency department (ED) use during pregnancy may be associated with worse obstetrical outcomes, possibly because of differences in access to health care. It is not known whether ED use before pregnancy is associated with serious adverse maternal and perinatal outcomes. OBJECTIVE To study the association between prepregnancy ED use and adverse maternal and perinatal outcomes. DESIGN, SETTING, AND PARTICIPANTS This population-based cohort study was conducted in Ontario, Canada, and included all liveb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…We previously described some reasons for maternal ED use before pregnancy, which were partly dominated by Main Discharge Diagnosis Groups of "Symptoms, signs, abnormal clinical and laboratory findings," as well as "Injury, poisonings, and consequences of external causes." 14 These findings are also consistent with a select number of considerably smaller studies showing an association between maternal and infant ED use in highly selective populations. 11,15 For example, among a cohort of 4112 Medicaid-insured mother-infant pairs attending a regional perinatal referral center in Delaware, the number of maternal ED visits was associated with infant ED use 6 months after birth, as were the number of maternal medications, young maternal age, and Black race.…”
Section: Other Studiessupporting
confidence: 82%
See 2 more Smart Citations
“…We previously described some reasons for maternal ED use before pregnancy, which were partly dominated by Main Discharge Diagnosis Groups of "Symptoms, signs, abnormal clinical and laboratory findings," as well as "Injury, poisonings, and consequences of external causes." 14 These findings are also consistent with a select number of considerably smaller studies showing an association between maternal and infant ED use in highly selective populations. 11,15 For example, among a cohort of 4112 Medicaid-insured mother-infant pairs attending a regional perinatal referral center in Delaware, the number of maternal ED visits was associated with infant ED use 6 months after birth, as were the number of maternal medications, young maternal age, and Black race.…”
Section: Other Studiessupporting
confidence: 82%
“…13 Even prepregnancy ED access is associated with a higher risk of severe maternal morbidity, severe neonatal morbidity, stillbirth, and neonatal death, especially as the number of prepregnancy ED visits increases. 14 Prior research observed a higher rate of ED encounters among infants whose mother was affected by a mental health problem or greater medical comorbidity, younger maternal age, and ED visits during pregnancy. 11,15 A major limitation of these studies is that they were restricted to commercially insured or low-income patients in the US, in contrast to regions with universal access to physician and hospital care, such as in Canada.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-institution studies have examined the incidence and reasons for emergency department visits and ICU admissions among pregnant and postpartum patients. [4][5][6][7][8][9][10][11] However, it is unknown whether these findings are generalizable across institutions and populations and to what extent hospital factors contribute to potentially avoidable postpartum ED visits. Therefore, we use a statewide data set to describe the patient and birth hospital characteristics associated with postpartum ED visits within 42 days of giving birth, including racial distribution by hospital type and most common diagnoses associated with postpartum ED visits.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions to improve communication and care coordination are limited by the lack of knowledge regarding which hospital settings should be targeted for these interventions. Single-institution studies have examined the incidence and reasons for emergency department visits and ICU admissions among pregnant and postpartum patients . However, it is unknown whether these findings are generalizable across institutions and populations and to what extent hospital factors contribute to potentially avoidable postpartum ED visits.…”
Section: Introductionmentioning
confidence: 99%